Study of the efficiency use of physical rehabilitation in patients with chronic gastritis - Kalmykov, S. A.; Urdina, G. S.; Pelikh, I. V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: to make physical rehabilitation program for patients with chronic gastritis type B, promotes normalization of gastric secretory function and prolong the period of remission. Objectives of the study was to assess the dynamics of gastric secretory function and functional status of the autonomic nervous system in patients with the chronic gastritis type B . Material: the study involved 37 women with a diagnosis of the chronic gastritis type B, increased acid gastric function. Results: it was established the positive influence of corrective exercises for the lower thoracic and lumbar spine, regulated breathing exercises based on the tone of the autonomic nervous system in combination with massage and diet therapy on the state of gastric secretory function. Conclusions : it is recommended to carry out therapeutic physical culture in the form of morning hygienic gymnastics, therapeutic exercises, self-study.